2016
DOI: 10.1038/srep37194
|View full text |Cite
|
Sign up to set email alerts
|

Ku70 Serine 155 mediates Aurora B inhibition and activation of the DNA damage response

Abstract: The Ku heterodimer (Ku70/Ku80) is the central DNA binding component of the classical non-homologous end joining (NHEJ) pathway that repairs DNA double-stranded breaks (DSBs), serving as the scaffold for the formation of the NHEJ complex. Here we show that Ku70 is phosphorylated on Serine 155 in response to DNA damage. Expression of Ku70 bearing a S155 phosphomimetic substitution (Ku70 S155D) in Ku70-deficient mouse embryonic fibroblasts (MEFs) triggered cell cycle arrest at multiple checkpoints and altered exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 72 publications
1
26
0
Order By: Relevance
“…In addition, we found that two of the three cyclin A2/CDK2 phosphorylation sites (T401 and T428) in human Ku70 are conserved in canine and mouse species. There are several reports describing cell cycle-dependent Ku70-localization and -function in human and rodent cells [7, 14, 24, 29]. Altogether, we speculate that Ku70-localization and -function in canine cells might be regulated by cell cycle dependent-phosphorylation, which will be validated in the future.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…In addition, we found that two of the three cyclin A2/CDK2 phosphorylation sites (T401 and T428) in human Ku70 are conserved in canine and mouse species. There are several reports describing cell cycle-dependent Ku70-localization and -function in human and rodent cells [7, 14, 24, 29]. Altogether, we speculate that Ku70-localization and -function in canine cells might be regulated by cell cycle dependent-phosphorylation, which will be validated in the future.…”
Section: Discussionsupporting
confidence: 64%
“…The location of the nuclear localization signal (NLS) sequence (NLS: 539-556), the two putative canonical sumoylation consensus motifs (ψ-K-X-E: 509 PKVE 512 and 555 PKVE 558 ) and the CDK phosphorylation motif ([S/T]Px[K/R]: 401 TPRR 404 ) in human Ku70 are shown [9, 18, 29]. The location of the primary candidate nucleophile required for 5′dRP/AP lyase activity (K31), the DNA-PK phosphorylation sites (S6 and S51), the DNA damage inducible phosphorylation sites (S27, S33 and S155), the putative phosphorylation sites required for Ku’s dissociation from DSB (T305, S306, T307, S314 and T316), the cyclin B1/CDK1 phosphorylation sites (T401 and T428), the cyclin A2/CDK2 phosphorylation sites (T401, T428 and T455), the putative cyclin E1/CDK2 phosphorylation site (T58), the ubiquitination site (K114), the acetylation sites (K317, K331, K338, K539, K542, K544, K553 and K556) and the two putative sumoylation sites (K510 and K556) in human Ku70 [1, 2, 4, 7, 9, 12, 26, 28, 29] are marked with asterisks., it has been reported that human Ku70 is modified by some PTMs, including acetylation, phosphorylation, sumoylation and ubiquitination [1, 2, 4, 7, 9, 12, 26, 29]. In addition, it is shown that human Ku70 has a nuclear localization signal (NLS) sequence spanning amino acids 539–556, two putative sumoylation consensus motifs (ψ-K-X-E: 509 PKVE 512 and 555 PKVE 558 ) and a CDK phosphorylation motif ([S/T]Px[K/R]: 401 TPRR 404 ) [9, 23, 29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Duolink II (Sigma-Aldrich Inc., St. Louis, MO, USA) in situ proximity ligation assay (PLA) was performed as previously described [ 48 ]. Cover slips were mounted onto glass slides with Prolong Gold antifade reagent with DAPI (Molecular Probes by Life Technologies, Burlington, ON, Canada) and were analyzed with an Olympus BX51 microscope (Olympus America Inc., Center Valley, PA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…AurB is also involved in the NHEJ pathway to repair DNA damage. Notably, the Ku heterodimer (Ku70/Ku80), a scaffolding protein of the NHEJ complex, represses AurB kinase activity after irradiation [ 114 ]. In response to DNA damage, PARP1 (poly(ADP-ribose) polymerase 1), a chromatin-associated DNA repair enzyme, also antagonizes AurB to block mitosis and histone H3 phosphorylation [ 115 ].…”
Section: Somatic Cellsmentioning
confidence: 99%